Solubility and thermodynamic functions of tebuconazole in nine organic solvents from T = (278.15 to 313.15) K and mixing properties of solutions. (March 2017) - Li, Yanxun; Li, Congcong; Cong, Yang; Du, Cunbin; Zhao, Hongkun
Graphical abstract: Highlights: Solubilities of tebuconazole in nine organic solvents were determined. The solubilities were correlated by using four thermodynamic models. The mixing properties of solution were computed based on Wilson model. Abstract: The solubility of tebuconazole in nine organic solvents including methanol, ethanol, isopropanol, n -propanol, ethyl acetate, toluene, acetone, 2-butanone and acetonitrile was determined experimentally by using the isothermal saturation method over a temperature range from (278.15 to 313.15) K under 101.2 kPa. For the temperature range investigated, the mole fraction solubility of tebuconazole in the solvents increased with a rise of temperature. On the whole, they obeyed the following order from high to low in different solvents: 2-butanone > acetone > (ethyl acetate, toluene) > methanol > ethanol > isopropanol >  n -propanol > acetonitrile. The acquired solubility data of tebuconazole in the studied solvents were correlated by using the modified Apelblat equation, λh equation, Wilson and NRTL models. The maximum values of root-mean-square deviation ( RMSD ) was 12.35 × 10 −4, and the relative average deviation ( RAD ), 1.56%. Generally, the four thermodynamic models could all be employed to describe the solubility behaviour of tebuconazole in these solvents, and the modified Apelblat equation correlated the experimental data best according to the result of Akaike Information Criterion ( AIC ) analysis. Furthermore, the mixing Gibbs energy, mixing enthalpy, mixing entropy, activity coefficient at infinitesimal concentration ( γ 1 ∞ ) and reduced excess enthalpy ( H 1 E, ∞ ) were computed. The solubility obtained and thermodynamic studies should be very helpful for optimizing the purification process of tebuconazole.